2021
DOI: 10.1182/blood-2021-149630
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndromes (MDS) Presenting with Isolated Thrombocytopenia: Characteristics, Outcomes, and Clinical Presentation Differences from Immune Thrombocytopenic Purpura (ITP)

Abstract: Introduction: Less than 5% of patients with MDS present with thrombocytopenia as an isolated abnormality (MDS-IT). There have been few systematic studies on MDS-IT and data regarding its course and prognosis are conflicting. Previous studies have defined MDS-IT based on the IPSS thresholds (Hb ≥10 g/dL; ANC ≥1.8×10 9/L; PLT <100×10 9/L). However, these were developed for prognostic, not diagnostic purposes which means that mild anemia and/or neutropenia might be present concomitantly with "isolated" thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…MDS presenting with thrombocytopenia as an isolated abnormality (MDS-IT) has not been described thoroughly and data regarding its diagnosis, progression and prognosis are still limited. Recent studies on MDS-IT cohorts showed that MDS-IT is commonly associated with multilineage dysplasia, favorable cytogenetics, lower-risk on prognostic scoring systems, high survival rate and a lower risk of AML evolution, compared to general MDS [51]. There are a few previous studies presenting the characteristics and natural history of MDS-IT, and comparing MDS-IT with other nonclonal disorders with isolated thrombocytopenia, especially ITP [51][52][53][54].…”
Section: Myelodysplastic Syndrome With Isolated Thrombocytopenia Mds-itmentioning
confidence: 99%
See 2 more Smart Citations
“…MDS presenting with thrombocytopenia as an isolated abnormality (MDS-IT) has not been described thoroughly and data regarding its diagnosis, progression and prognosis are still limited. Recent studies on MDS-IT cohorts showed that MDS-IT is commonly associated with multilineage dysplasia, favorable cytogenetics, lower-risk on prognostic scoring systems, high survival rate and a lower risk of AML evolution, compared to general MDS [51]. There are a few previous studies presenting the characteristics and natural history of MDS-IT, and comparing MDS-IT with other nonclonal disorders with isolated thrombocytopenia, especially ITP [51][52][53][54].…”
Section: Myelodysplastic Syndrome With Isolated Thrombocytopenia Mds-itmentioning
confidence: 99%
“…Recent studies on MDS-IT cohorts showed that MDS-IT is commonly associated with multilineage dysplasia, favorable cytogenetics, lower-risk on prognostic scoring systems, high survival rate and a lower risk of AML evolution, compared to general MDS [51]. There are a few previous studies presenting the characteristics and natural history of MDS-IT, and comparing MDS-IT with other nonclonal disorders with isolated thrombocytopenia, especially ITP [51][52][53][54]. A summary of the studies on MDS-IT and their main findings regarding patient characteristics, diagnostic and prognostic features are presented in Table 3.…”
Section: Myelodysplastic Syndrome With Isolated Thrombocytopenia Mds-itmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Isolated thrombocytopenia was present in 5% of MDS patients and is associated with a favorable prognosis. 6,7 In two CCUS cohorts, the prevalence of isolated thrombocytopenia was reported to be 0 and 11%. 8,9 The significance of CCUS associated with isolated thrombocytopenia is not known.…”
Section: Introductionmentioning
confidence: 99%
“…While older adults with isolated thrombocytopenia are more likely to be diagnosed with a hematologic malignancy than those with normal platelet counts, isolated thrombocytopenia is uncommon in myelodysplastic syndrome (MDS) and CCUS 5 . Isolated thrombocytopenia was present in 5% of MDS patients and is associated with a favorable prognosis 6,7 . In two CCUS cohorts, the prevalence of isolated thrombocytopenia was reported to be 0 and 11% 8,9 .…”
Section: Introductionmentioning
confidence: 99%